(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of knowledge, practice and some related factors on prevention and treatment of exposure to sharp objects of health students at Phenikaa University in 2024. Subjects and methods: Cross-sectional study design on 200 students of course K14-16, Faculty of Nursing, Phenikaa University, from November 2023 to April 2024. The interview toolkit was designed based on the content on prevention and treatment of sharp objects. Results: The percentage of students with general knowledge on prevention and treatment of exposure to sharp objects was 53.0%. The study showed that knowledge was related to general practice on prevention and treatment of sharp objects. Conclusion: General knowledge of prevention and treatment of sharp objects is at an average level. It is necessary to improve awareness of learning in class, in the practice room and in the hospital clinic as well as self-study to update knowledge, thereby having correct knowledge of prevention and treatment of exposure to sharp objects.